Greenhouse Gas Emissions and Economic Growth in Africa: Does Financial Development Play any Moderating Role? - Tsaurai, Kunofiwa (International Journal of Energy Economics and Policy, 2018)
The study had two major objectives. Firstly, to investigate the influence of greenhouse gas emissions on economic growth. Secondly, to find out if the interaction between greenhouse gas emissions and financial development enhanced economic growth in Southern and Western African nations. Four econometric estimation methods, namely dynamic generalised methods of moments (GMM), pooled ordinary least squares (OLS), fixed and random effects were used with annual data ranging from 2001 to 2012. The impact of greenhouse gas emissions on economic growth was found to be non-significant positive (pooled OLS), non-significant negative (fixed and random effects) and significant positive (dynamic GMM). The interaction between greenhouse gas emissions and financial development was found to have had a significant positive effect on economic growth under the dynamic GMM, fixed and random effects. The non-significant positive influence of greenhouse gas emissions on economic growth is a finding produced by the pooled OLS regression approach. Keywords: Greenhouse Gas Emissions; Economic growth; Africa JEL Classificiations: F43; N27; Q5 DOI: https://doi.org/10.32479/ijeep.6988